2017
DOI: 10.13080/z-a.2017.104.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic behaviour of qualitative and seed yield-related traits in Brassica rapa

Abstract: Please use the following format when citing the article: Mumtaz A., Sadaqat H. A., Saeed M., Yousaf M. I., Shehzad A., Ahmed H. AbstractThe domestic production of edible oil meets only 20.23% of the demand in Pakistan, and domestic oil production needs to be increased. Thanks to its short life cycle, high yield and yellow seed colour, oilseed rape (Brassica rapa L.) is a potentially useful source to fill the gap between production and consumption. This study was designed to ascertain the genetic expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The reasons for this situation are low quality fodder and limited feed availability. Because of low quality fodder and feed, animals reach puberty later, and the intercalving interval is shorter (Ali, 2011;Mumtaz et al, 2017b). This situation could be improved with increased milk and meat productivity per animal, and increased chicken production, and targets could be achieved by increasing milk, meat and chicken production up to 100% with good quality fodder and feed availability.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this situation are low quality fodder and limited feed availability. Because of low quality fodder and feed, animals reach puberty later, and the intercalving interval is shorter (Ali, 2011;Mumtaz et al, 2017b). This situation could be improved with increased milk and meat productivity per animal, and increased chicken production, and targets could be achieved by increasing milk, meat and chicken production up to 100% with good quality fodder and feed availability.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, existing B. rapa varieties are have limitations such as a low yield, aphid attack, white rust of crucifer, low percentage of better quality oil, and shattering at maturity. Additionally, lodging problem due to winds and rains is also a major limitation (Mumtaz et al, 2014). Farmers are also reluctant to grow it due to problems in its economic return but with such varieties of high yielding and short duration, its area and production can be increases and farmers can be attracted towards it.…”
Section: Introductionmentioning
confidence: 99%
“…The cross of dark green and light green (A11 × A8, A17 × A8) produces green leaves. Mumtaz et al, 2017 also found descriptive traits inheritance in Brassica rapa.…”
Section: Descriptive Traits In Sunflower 1) Leaf Colormentioning
confidence: 77%